Penetrance of a rare familial mutation predisposing to papillary thyroid cancer - Saporito, Donika (Fam Cancer, 2018)
Familial non-medullary thyroid cancer (FNMTC) is clinically defined as two or more first-degree relatives with NMTC and appears to follow an autosomal dominant inheritance pattern. Approximately 5–7% of NMTC is hereditary and affects multiple generations with a young age of onset. The primary aim of this study was to determine the age-specific penetrance of NMTC in individuals from a large family with FNMTC with a previously identified private mutation at 4q32, with a secondary aim to determine the penetrance for benign thyroid disease in this family. We present a large family with NMTC in which we had previously described a culpable mutation. Participants provided their personal medical history and family history. The germline 4q32 A > C mutation was detected in 34 of 68 tested individuals. Age-specific penetrance of thyroid cancer and benign thyroid disease was determined using the inverted Kaplan–Meier method of segregation analysis. Individuals who tested positive for the 4q32 mutation have a 68.9% (95% CI 46.5–88.7) risk of developing thyroid cancer by age 70 and a 65.3% (95% CI 46.0–83.8) risk of developing benign thyroid disease by age 70. The 4q32 A > C mutation significantly increases the risk to develop thyroid cancer but not benign thyroid disease in members of this family. The female:male sex ratio of 1.33 that we observed in affected mutation carriers differs greatly from the ratio of approximately 3:1 observed in PTC, supporting a central role of the mutation. Early thyroid surveillance with annual ultrasound is recommended to individuals testing positive for this private familial mutation.